A Stitch in Time Saved Nine: Early Recognition of Propofol Infusion Syndrome under Anesthesia - Bithal, Parmod K.; Ahmad, Gazi P.; Daniel, Vandan W. (Journal of Neuroanaesthesiology and Critical Care, 2019)
Though propofol infusion syndrome results from a larger dose of infusion over a longer period of time, we observed its development even when it was infused for a shorter period of time. In our patient, it was heralded by progressive acidosis and hyperkalemia. Discontinuation of propofol and simultaneous treatment of hyperkalemia averted any harm to the patient.
Keywords: propofol infusion syndrome; hyperkalemia; acidosis